Framework to Define Structure and Boundaries of Complex Health Intervention Systems: The ALERT Project - Boriani, Elena; Esposito, Roberto; Frazzoli, Chiara; Fantke, Peter; Hald, Tine; Rüegg, Simon R. (Frontiers in Public Health, 2017)
Health interventions systems are complex and subject to multiple variables in different phases of implementation. This constitutes a concrete challenge for the application of translational science in real life. Complex systems as health oriented interventions call for interdisciplinary approaches with carefully defined system boundaries. Exploring individual components of such systems from different viewpoints gives a wide overview and helps to understand the elements and the relationships that drive actions and consequences within the system. We present an application and assessment of a framework with focus on systems and system boundaries of interdisciplinary projects. As an example on how to apply our framework, we analyzed ALERT (An integrated sensors and biosensors system (BEST) aimed at monitoring the quality, health and traceability of the chain of the bovine milk), a multidisciplinary and interdisciplinary project based on the application of measurable biomarkers at strategic points of the milk chain for improved food security (including safety), human and ecosystem health. In fact, the European food safety framework calls for science-based support to the primary producers’ mandate for legal, scientific, and ethical responsibility in food supply. Because of its multidisciplinary and interdisciplinary approach involving human, animal and ecosystem health ALERT can be considered as a One Health project. Within the ALERT context as example we identified the need to take into account the main actors, interactions and relationships of stakeholders in order to depict a simplified skeleton of the system. The framework can provide elements to highlight how and where to improve the project development when project evaluations are required.